2021
DOI: 10.1080/14647893.2021.1940916
|View full text |Cite
|
Sign up to set email alerts
|

Is the health risk and consequence of generalised joint hypermobility understood within a classical ballet narrative? Concerns for dance practitioners

Abstract: Generalised Joint Hypermobility (GJH) is a heritable disorder of the connective tissue that manifests as extreme range of motion in the joints; it is considered both an asset and health risk to the dancer. Recently, links between GJH, anxiety, emotional and mental wellbeing have been established. The experiences of GJH in professional dance artists (five male, four female; mean age = 32.3 yrs; range = 25-40 yrs) and Ballet masters (3 female & 1 male, mean experience 30.8 yrs.) were exploredthrough semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…For example, Steinberg and co-workers recommended that the dancers maintain their natural flexibility through appropriate joint exercises instead of increasing ROMs [35]. Forczek-Karkosz et al [36] measured and suggested the ROMs of anterior pelvic, hip, and knee for flamenco dancers, and the effects of joint hypermobility on ballet dancers were investigated [37]. The hidden Markov model expressed the angular movements in Likok Pulo, Aceh traditional dance [38].…”
Section: Smartphone-based Inclinometer and Goniometersmentioning
confidence: 99%
“…For example, Steinberg and co-workers recommended that the dancers maintain their natural flexibility through appropriate joint exercises instead of increasing ROMs [35]. Forczek-Karkosz et al [36] measured and suggested the ROMs of anterior pelvic, hip, and knee for flamenco dancers, and the effects of joint hypermobility on ballet dancers were investigated [37]. The hidden Markov model expressed the angular movements in Likok Pulo, Aceh traditional dance [38].…”
Section: Smartphone-based Inclinometer and Goniometersmentioning
confidence: 99%